Ecological and Recreational Corridor Bogotá Mountain Reserve - Wiesner, Diana (project baikal, 2013)
Bogotá the capital of the Republic of Colombia is a tropical highland city located at 2650 m above sea level, the 25th largest city of the world and among the large, one of the highest. A proposal for integration of components of ecological networks in the Oriental Hills of Bogotá, along a gradient from wild to built nature. Name as The Bogotá Ecological and Recreational Corridor (C.E.R.) is based on three strategies: first a social being the largest border agreement with 53 km, along the entire eastern limit of the city. Second the biophysical which involves restoration of ecosystem, and third the socio-spatial which includes infrastructure for making an open air museum for integration and urban limit. The ultimate aim of the approach is to contribute as a pilot proposal in biodiversity managment and cultural transformation in ecological issues for the inhabitants.